Lip service: Histological phenotypes correlate with diet and feeding ecology in herbivorous pacus. Issue 2 (13th October 2022) - Cohen, Karly E.; Lucanus, Oliver; Summers, Adam P.; Kolmann, Matthew A.
Abstract: Complex prey processing requires the repositioning of food between the teeth, as modulated by a soft tissue appendage like a tongue or lips. In this study, we trace the evolution of lips and ligaments, which are used during prey capture and prey processing in an herbivorous group of fishes. Pacus (Serrasalmidae) are Neotropical freshwater fishes that feed on leaves, fruits, and seeds. These prey are hard or tough, require high forces to fracture, contain abrasive or caustic elements, or deform considerably before failure. Pacus are gape‐limited and do not have the pharyngeal jaws many bony fishes use to dismantle and/or transport prey. Despite their gape limitation, pacus feed on prey larger than their mouths, relying on robust teeth and a hypertrophied lower lip for manipulation and breakdown of food. We used histology to compare the lip morphology across 14 species of pacus and piranhas to better understand this soft tissue. We found that frugivorous pacus have larger, more complex lips which are innervated and folded at their surface, while grazing species have callused, mucus‐covered lips. Unlike mammalian lips or tongues, pacu lips lack any intrinsic skeletal or smooth muscle. This implies that pacu lips lack dexterity; however, we found a novel connection to the primordial ligament which suggests that the lips are actuated by the jaw adductors. We propose that pacus combine hydraulic repositioning of prey inside the buccal cavity with direct oral manipulation, the latter using a combination of a morphologically heterodont dentition and compliant lips for reorienting food.